Maraval Reservior, Trinidad, B.W.I. - (:unkn) unknown (D.Adamson,[Trinidad and Tobago], 2011)
The postcard shows the Maraval Reservoir which was first established in 1850s to provide pipe bourne water to Port of Spain and its environs by order of the then Governor, Lord Harris.
Colour: Sepia; Style; Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Reservoirs--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Maraval; Architecture--Trinidad and Tobago; Plants, Potted--Trinidad and Tobago; [1907]